2021
DOI: 10.3390/genes12071042
|View full text |Cite
|
Sign up to set email alerts
|

Parentage Analysis in Giant Grouper (Epinephelus lanceolatus) Using Microsatellite and SNP Markers from Genotyping-by-Sequencing Data

Abstract: Pedigree information is necessary for the maintenance of diversity for wild and captive populations. Accurate pedigree is determined by molecular marker-based parentage analysis, which may be influenced by the polymorphism and number of markers, integrity of samples, relatedness of parents, or different analysis programs. Here, we described the first development of 208 single nucleotide polymorphisms (SNPs) and 11 microsatellites for giant grouper (Epinephelus lanceolatus) taking advantage of Genotyping-by-seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 81 publications
1
11
0
Order By: Relevance
“…In this study, the chip was employed to conduct a clustering analysis of 60 Langshan roosters with documented pedigree information. The results showed that all siblings were accurately clustered, which is consistent with previous findings [30]. Collectively, these results indicate that the chip developed in this study holds great potential for genetic research on local chicken populations.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the chip was employed to conduct a clustering analysis of 60 Langshan roosters with documented pedigree information. The results showed that all siblings were accurately clustered, which is consistent with previous findings [30]. Collectively, these results indicate that the chip developed in this study holds great potential for genetic research on local chicken populations.…”
Section: Discussionsupporting
confidence: 91%
“…The two different datasets may have differences in data resolution and therefore this may account for some of the differences in the results. However, studies evaluating the performance of SNPs versus microsatellites found high power to resolve relatedness and parentage when using 100-500 SNPs, and results between the two types of data were highly congruent (Flanagan and Jones 2019;Premachandra et al 2019;Weng et al 2021). Despite the congruence of the two datasets, we note that there may be inherent variation in their results due to the differences in genetic approach, thus care should be taken when comparing them.…”
Section: Shifts In Reproductive Behaviourmentioning
confidence: 68%
“…Nevertheless, the tested markers proved to be more helpful than those used for parentage analysis in the wild boar ( S. scrofa ) [ 62 ] and goat ( Capra hircus ) [ 63 ] populations. However, the evaluation of the microsatellite markers used for the pedigree analysis in plateau pika ( Ochotona curzoniae ) [ 64 ] and giant grouper ( Epinephelus lanceolatus ) [ 65 ] showed better values than those obtained by us. This is further proof that the YWLL46 should be removed, because this marker underestimates the values in every analysis.…”
Section: Discussionmentioning
confidence: 92%